2006
DOI: 10.1051/0004-6361:20066365
|View full text |Cite
|
Sign up to set email alerts
|

Pulsation in the atmosphere of the roAp star HD 24712

Abstract: Aims. We have investigated the structure of the pulsating atmosphere of one of the best studied rapidly oscillating Ap stars, HD 24712. Methods. For this purpose we analyzed spectra collected during [2001][2002][2003][2004]. An extensive data set was obtained in 2004 simultaneously with the photometry of the Canadian MOST mini-satellite. This allows us to connect directly atmospheric dynamics observed as radial velocity variations with light variations seen in photometry. Results. We directly derived for the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 29 publications
4
86
0
Order By: Relevance
“…These measurements agree closely with the results obtained for the same stars at other telescopes (e.g. Ryabchikova et al 2007;Ilyin 2012). Repeated observations of a very slowly rotating Ap star γ Equ reveals no systematic differences in the Stokes V profiles during the entire period of our observations of II Peg.…”
Section: Spectropolarimetric Observationssupporting
confidence: 91%
“…These measurements agree closely with the results obtained for the same stars at other telescopes (e.g. Ryabchikova et al 2007;Ilyin 2012). Repeated observations of a very slowly rotating Ap star γ Equ reveals no systematic differences in the Stokes V profiles during the entire period of our observations of II Peg.…”
Section: Spectropolarimetric Observationssupporting
confidence: 91%
“…The variability period found by Preston (1972) was confirmed by photometric observations by Wolff & Morrison (1973). Many studies of the magnetic field of HD 24712 have been carried out (Preston 1972;Brown & Landstreet 1981;Mathys 1991Mathys , 1994Mathys & Hubrig 1997;Ryabchikova et al 1997;Leone et al 2000;Wade et al 2000a;Leone & Catanzaro 2004;Ryabchikova et al 2005Ryabchikova et al , 2007. Below we will use some of these measurements for improving the rotational period of the star.…”
Section: Hd 24712mentioning
confidence: 63%
“…Spectroscopic and photometric techniques are able to provide information about the different pulsation modes and hence about the atmospheric layers at different optical depths in the stellar atmosphere. Some investigators (e.g., Ryabchikova et al 2007) have used radial velocity amplitudes of different spectral lines, which are measured from spectroscopic data, as a function of optical depth to describe the properties of pulsational waves in the atmospheric layers where these spectral lines are formed. Although this type of analysis is only possible for a few bright roAp stars, such investigations have demonstrated that for understanding the phenomenon of roAp stars a good knowledge of the vertical structure of their surface layers is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The observations and data reduction were described by Ryabchikova et al (2007b). The spectrum was observed close to magnetic maximum, which coincides roughly with the REE spectral line intensity maximum.…”
Section: Praseodymium In the Roap Star Hd 24 712mentioning
confidence: 67%
“…HD 24 712 possesses a magnetic field with a mean magneticfield modulus B that increases from 2.5 kG at magnetic minimum to ∼3.1-3.3 kG at magnetic maximum (Ryabchikova et al 2007b). We ignore the influence of the magnetic field on atmospheric structure, based on the results of Kochukhov et al (2005) who demonstrated that the difference in temperature and gas pressure distributions between magnetic and non-magnetic model atmospheres with T eff = 8000 K does not exceed 30 K and 6%, respectively, for field strengths smaller than 5 kG.…”
Section: Programs and Model Atmospheresmentioning
confidence: 99%